Hubungan Panjang Badan Lahir dengan Perkembangan Anak Usia 3-24 Bulan di Kabupaten Gunungkidul Tahun 2017 - Rikha Galih Nurmalasari; Yani Widyastuti; Margono Margono (Jurnal Kesehatan Ibu dan Anak, 2017)
Development is the increasing ability of complex body functions, as a result of the maturation process. Development influenced byseveral factors, one of which is the nutrition or growth of fetus since in the uterus. One of the nutritional status assessment is bylooking at the indicator of body length. Children who have low birth length are possibility to experience developmental delay, whichwill adversely affect the child's development. This study aims to determine the relationship of birth length with children developmentage 3-24 month in Gunungkidul Regency 2017. The design of this study is observational analytic with Retrospective Cohort design.This research was held from March to May 2017 in the working area of Public Health Centers Karangmojo I and Semanu I, usingpurposive sampling technique that the respondent is children with low birth length as many as 106 children and respondents withnormal birth length as many as 106 children. Data collection by looking at the Maternal and Child Health book or Card Toward Healthand developmental test directly implemented using Denver II. Hypothesis test is using chi-square analysis at 95% confidence level.The results showed children that experiencing developmental disorders as many as 45 (42.46%) respondents with low birth lengthand 22 (20,75%) respondents with normal birth length, with p-value 0.001 and RR 2 (95% CI 1.327-3.154). This research can beconcluded that there is a relationship of birth length with children development age 3-24 month and children with low birth length havea twofold greater risk to experience developmental disorders than normal birth length children.